Indirect Speech Act as a Linguistic and Social and Cultural Phenomenon (Proceedings of Southern Federal University. Philology, 2017)
Kirill S. Neustroev (Rostov-on-Don, Russian Federation)In this article we analyze as the problem of distinguishing direct / indirect speech act nomination is covered in linguistic pragmatics and language philosophy. The Semantic nature of indirect speech acts is revealed based on the theory of illocution and implicatures. From the linguistic point of view the notion of indirect expressing the illocutionary meaning is in certain degree contradictory what, in fact, is reflected in the theoretical positions of the investigators dealing with this problem In numerous theoretical conceptions the utterance is interpreted as the pragmatic sphere of tension between the semantic content and the illocutionary force expressed. At the same time the high frequency of indirect speech acts as conventional means of impact upon the addressee in various discourse types doesn’t get the optimal theoretical justification in the investigators’ works.The indirect speech act nomination character of the speaking subject’s intentions is understood in the article as the complex discursive phenomenon which is originally connected not only with the politeness, but also with the high degree of positivity in the interrelations between the interlocutors, their aspiration of setting and maintaining the phatic contact with each other. In the hierarchy of the factors predetermining the indirect speech act nomination of the speaker’s intention, the relevancy of this intention realization includes trusting relationships between the interlocutors, the category of politeness and the vagueness of the current discursive need presentation.Key words: linguistic pragmatics, language philosophy, speech act nomination, indirect speech act, illocutionary act, context, implicature. DOI 10.23683/1995-0640-2017-3-96-102